Performance measurement and its impact on Brazilian public academic libraries. (September 2019) - Celere, Milena; Mendes, Glauco Henrique de Sousa; Ganga, Gilberto Miller Devós; Martins, Roberto Antonio
Assessment and measurement of performance in academic libraries are well established. However, in developing countries such as Brazil, this has not been fully explored. This study aims to contribute to the knowledge by investigating practices of measuring library performance in Brazilian public academic libraries and analyzing their relationship with managerial processes. It employs a survey method with a descriptive-explanatory objective and follows a quantitative research approach. Data was gathered from 149 libraries. Results indicate that performance measurement system at academic libraries in Brazil lack systematic methods. However, libraries with implemented performance management systems have better management practices, reflecting in their library management maturity.